Immunomodulatory Activities of a Fungal Protein Extracted from Hericium erinaceus through Regulating the Gut Microbiota - Diling, Chen; Chaoqun, Zheng; Jian, Yang; Jian, Li; Jiyan, Su; Yizhen, Xie; Guoxiao, Lai (Frontiers in Immunology, 2017)
A single-band protein (HEP3) was isolated from Hericium erinaceus using a chemical separation combined with pharmacodynamic evaluation methods. This protein exhibited immunomodulatory activity in lipopolysaccharide-activated RAW 264.7 macrophages by decreasing the overproduction of tumor necrosis factor-α, interleukin (IL)-1β, and IL-6, and downregulating the expression of inducible nitric oxide synthase and nuclear factor-κB p65. Further researches revealed that HEP3 could improve the immune system via regulating the composition and metabolism of gut microbiota to activate the proliferation and differentiation of T cells, stimulate the intestinal antigen-presenting cells in high-dose cyclophosphamide-induced immunotoxicity in mice, and play a prebiotic role in the case of excessive antibiotics in inflammatory bowel disease model mice. Aided experiments also showed that HEP3 could be used as an antitumor immune inhibitor in tumor-burdened mice. The results of the present study suggested that fungal protein from H. erinaceus could be used as a drug or functional food ingredient for immunotherapy because of its immunomodulatory activities.